Pengentasan Kemiskinan dalam Pandangan Al-Qur’an dan Hadits - Muhammad Ali Musafak (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2019)
There is no doubt that poverty is a great danger to religious beliefs. As the saying of Rasullah peace be upon him